Role of Tamsulosin in Clearance of Upper Ureteral Calculi After Extracorporeal Shock Wave Lithotripsy: A Randomized Controlled Trial - Singh, Santosh Kumar; Pawar, Devendra Singh; Griwan, Mahavir Singh; Indora, Jag Mohan; Sharma, Sachit (Urology Journal, 2011)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Purpose: To evaluate the role of tamsulosin in stone clearance in patients with upper ureteral stone after extracorporeal shock wave lithotripsy (SWL). Materials and Methods: This randomized controlled trial was performed on 117 patients with a single upper ureteral calculus undergoing SWL. The study group received 0.4 mg tamsulosin daily while the control group received hydration and analgesic on demand for a maximum of 3 months. Follow-up visits were performed at 1, 2, and 3 months after SWL. Efficiency of tamsulosin was evaluated in terms of success rate, time for expulsion of fragments, number of SWL sessions, incidence of steinstrasse, and pain intensity. Results: The clearance rate after 1, 2, and 3 months were higher in tamsulosin group than the control group (85%, 89.8%, and 91.5% versus 70.6%, 79.3%, and 86.2%; P = .01, P = .11, and P = .34, respectively). The mean time for expulsion of the fragments was 26.78 ± 11.96 days and 31.28 ± 18.31 days in tamsulosin and control groups, respectively (P = .138). Steinstrasse developed in 8 patients in tamsulosin group and in 13 patients in control group (P = .167). Visual analogue scale pain score was 24.92 ± 7.57 in tamsulosin group and 41.81 ± 17.24 in control group (P = .000). Conclusion: Tamsulosin helps in clearance of upper ureteral stones after 1 month of SWL, particularly stones with size of 11 to 15 mm with less requirement of SWL sessions and analgesics.